2002
DOI: 10.1111/1467-6451.00181
|View full text |Cite
|
Sign up to set email alerts
|

Retail Strategies on the Web: Price and Non–price Competition in the Online Book Industry

Abstract: Two conflicting predictions have emerged regarding the effect of low–cost information on price. The first states that all Internet retailers will charge the same low price for mass produced goods. The second states that Internet retailers will differentiate to avoid intense price competition. Using data collected in April 1999 on the prices of 107 books in thirteen online and two physical bookstores, we find similar average prices online and in physical stores and substantial price dispersion online. Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
167
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(183 citation statements)
references
References 12 publications
12
167
2
2
Order By: Relevance
“…Brynjolfsson and Smith (2000) find substantial dispersion for prices of books and CDs on the Internet, to an extent that is roughly comparable to that in offline markets. Clay et al (2003) report similar findings for the online book market. Chevalier and Goolsbee (2003) find that book prices are much more variable online than in retail stores.…”
Section: Related Literaturesupporting
confidence: 69%
“…Brynjolfsson and Smith (2000) find substantial dispersion for prices of books and CDs on the Internet, to an extent that is roughly comparable to that in offline markets. Clay et al (2003) report similar findings for the online book market. Chevalier and Goolsbee (2003) find that book prices are much more variable online than in retail stores.…”
Section: Related Literaturesupporting
confidence: 69%
“…We have reproduced their table in this paper as Table 2, with modifications. Although some studies have found that online price dispersion is higher than offline price dispersion (e.g., Bailey 1998, Erevelles et al 2001, Clay et al 2002, others have found that online dispersion is lower than offline dispersion (e.g., Scott-Morton et al 2001, Ancarani and Shankar (2004) (standard deviation) Chellappa et al 2007 Scholten andSmith (2002) Source. Pan et al (2004) with modifications.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…For example, Clay, Krishnan, and Wolff (2001) find that competition leads to lower prices and lower price dispersion, and that widely advertised items have lower prices. Clay, Krishnan, Wolff, and Fernandes (2002) find that even though the average prices are similar between online and physical stores, price dispersion is greater for the former, indicating that online firms do not charge the same prices. Chevalier and Goolsbee (2003) use reported sales ranks to proxy quantity and estimate demand and price indices for books sold at the Amazon and Barnes & Noble websites.…”
Section: General and Academic Publishingmentioning
confidence: 79%